MINIMALISASI SAMPAH PLASTIK DI KAMPUNG JAWA MELALUI GERAKAN “DIET SAMPAH PLASTIK” - Karina Karina; Taufiq Ihsan (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Plastic has become a thing that we often encounter in everyday life. Various household appliances, cutlery, school equipment, and others still make plastic as the primary material. Plastic waste is the most challenging rubbish to be decomposed by soil naturally. Even in the span of years, the land will not succeed in breaking down plastic waste into organic compounds that can be reused by nature. Contrary to this, the consumption of plastic goods continues to increase every year, not least in the village of Kampung Jawa, Solok City. People who still choose to use plastic materials are the leading cause of the large amount of plastic waste produced by this village office. Through the Community Student Service Andalas University 2018, the